Assessment and correction SRTM DEM with reference to geo-hazard identification in the Cameron Highlands, Malaysia - Ahmad, Baharin (2007)
This research assesses the accuracy of SRTM DEMs acquired over the mountainous-hillands of Cameron Highlands with DEMs generated from Digital Aerial Photograph (DAP) with a fine (2 m) spatial resolution and height resolution of about 0.5 m. The ground control points used for generating stereo models from the DAP were acquired during field work using GPS which achieved accuracy better than 2 cm in most cases. To overcome the difficulty of overlaying the DEMs with the DAP DEM as no features can be easily identified on both the images, therefore a technique of using transects and contours generated from the DEMs were used to correct the horizontal displacement. These then allowed an analysis of the height accuracy to be undertaken. The height of SRTM DEM was also corrected by applying Linear Regression Models. These models were produced by comparing pixels obtained from points, profiles and an area. Once again the corrected DEMs were assessed. Finally the extracted profiles and contours from the corrected SRTM DEM were compared with the reference DEM. From the comparisons, the horizontal errors of the SRTM DEMs were found to be about one and the half pixels (â‰ˆ140 m) to the east. The SD of height differences using 90% data were 9.2 m from the profile comparisons; 10.4 m from the pixel area comparisons and 10.8 m from GPS GCPs comparison. From the three comparisons, the means of the height differences were 5.2 m, 6.1 m and 15.2 m. When the corrections were applied the generated contours from the SRTM DEM were close to the DAP reference contours. Using contour colours images and height modelling, the corrected DEM was found to have the potential to detect areas that prone to flash floods and mudslides.